2022
DOI: 10.21037/atm-22-506
|View full text |Cite
|
Sign up to set email alerts
|

Textbook outcome after minimally invasive esophagectomy is an important prognostic indicator for predicting long-term oncological outcomes with locally advanced esophageal squamous cell carcinoma

Abstract: Background: The textbook outcome (TO) emerges as a novel prognostic factor in surgical oncology.The present study aimed to evaluate the effect of TO on the risk of death and recurrence in patients with esophageal squamous cell carcinoma (ESCC) after minimally invasive esophagectomy (MIE). Methods:The study involved retrospective analysis of 528 patients with ESCC who were subjected to MIE from January 2011 to December 2017. TO included 8 parameters: complete resection; microscopically tumor-negative resection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…But it is not surprising that the overall complication rate reached 49%. In a recent benchmarking study from the Esophageal Complications Consensus Group (ECCG)’s large database (ESODATA), 59% of patients developed postoperative complications, with PPC the most represented group (27.8% in 1,595 patients) ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…But it is not surprising that the overall complication rate reached 49%. In a recent benchmarking study from the Esophageal Complications Consensus Group (ECCG)’s large database (ESODATA), 59% of patients developed postoperative complications, with PPC the most represented group (27.8% in 1,595 patients) ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant progress in multimodal therapy (Neoadjuvant chemoradiotherapy and postoperative adjuvant), the 5‐year overall survival (OS) of patients with ESCC is still poor (about 25%) [2]. It has been found that in addition to the tumor characteristics (T stage and N stage), the quality of surgery is also an essential factor leading to poor prognosis of patients [3, 4].…”
Section: Introductionmentioning
confidence: 99%